Knowledge sharing behaviour in libraries: a case study of Raja Tun Uda Library Selangor, Malaysia - Mat Isa, Azman; Mohd Jemal, Nurul Farhana; Mohd Nordin, Nordiana (2016)
Knowledge management is adopted by many organizations in order to improve their performance and gain competitive advantage. Knowledge sharing has become a crucial activity in knowledge management.Being at the core of information management, librarians should demonstrate considerable level of knowledge management practice.This study investigates factors affecting knowledge sharing behavior in a state library namely, Raja Tun Uda Library, Selangor.It aims to identify relationships between individual, organizational and technological factors with knowledge sharing behavior in the organization.Data were collected using questionnaires and analyzed using Statistical Package for Social Science version 16.The findings show that individual and technological factors have significant relationships with knowledge sharing behavior.However, there is no significant relationship between organizational factors and knowledge sharing behavior.